Energy transition and path dependence: the case of Costa Rica - García Sánchez, Daniela; Avendaño Leadem, Daniel (Revista Geográfica de América Central., 2018)
Costa Rica’s world known renewable energy model relies heavily on large scale hydropower, a source surrounded by strong environmental and social questionings. This condition of dependence has its own reinforcing processes that hinder advancements of alternative renewable technologies. In today’s carbon-constrained world, new approaches – and new geographies – are required to ensure the availability and accessibility of sustainable energy services. Using path dependence theory developed within evolutionary economic geography and neoinstitutionalist school of thought, the present research offers an explanation of the specific path driven by the impact of historical events that favor hydropower in Costa Rica’s energy transition.